Guide Catheter-Induced Aortic Dissection Complicated by Pericardial Effusion with Pulsus Paradoxus: A Case Report of Successful Medical Management - Magdalene Fiddler; Sriya A. Avadhani; Jonathan D. Marmur (Case Reports in Medicine)
Aortic dissection is a rare but potentially fatal complication of percutaneous coronary intervention (PCI). Management strategies of PCI induced dissection are not clearly identified in literature; such occurrences often mandate surgical repair of the aortic root with reimplantation of the coronary arteries. Another trend seen in case reports is the use of coronary-aortic stenting if such lesions permit. Several factors impact the management decision including the hemodynamic stability of the patient; mechanism of aortic injury; size, severity, and direction of propagation of the dissection; presence of an intimal flap; and preexisting atherosclerotic disease. We describe a case of a 65-year-old woman who underwent PCI for a chronic right coronary artery (RCA) occlusion, which was complicated by aortic dissection and pericardial effusion. Our case report suggests that nonsurgical management may also be appropriate for PCI induced dissections, and potentially even those associated with new pericardial effusion.